Juvenile dermatomyositis associated with partial lipodystrophy - Amjad, Muhammad; Mashhood, Asher Ahmed (Journal of Pakistan Association of Dermatologists, 2017)
Dermatomyositis with its cutaneous, myopathic and other systemic manifestations stand a high chance of malignancy in adults, but in children it has a rather benign and prolonged course and may have a number of late sequelae. We present here a case of juvenile dermatomyositis with partial lipodystrophy as a late sequel. Â